Combined arthroscopic rotator cuff repair leads to better clinical outcomes than isolated removal of calcific deposits for shoulder calcific tendinitis: A 2- to 5-year follow-up study - Pang, Long; Li, Tao; Li, Yinghao; Cao, Yuanyinuo; Li, Jian; Zhu, Jing; Tang, Xin (Frontiers in Surgery, 2022)
Purpose The optimal treatment procedure for shoulder calcific tendinitis (CT) remains controversial. This study aimed to assess the efficacy of arthroscopic treatment for CT, and to compare the clinical outcomes following combined rotator cuff repair and isolated removal of calcific deposits. Methods A total of 23 shoulders underwent combined rotator cuff repair (repair group), and 24 shoulders underwent isolated removal of calcific deposits (debridement group). The clinical outcomes were evaluated at baseline, 3 months, 6 months, and 12 months after the surgery and annually thereafter. The efficacy measures included the visual analog scale (VAS) pain score, American Shoulder and Elbow Surgeons (ASES) score, University of California at Los Angeles (UCLA) score and radiographic outcomes. Results Remarkable improvement in clinical outcomes at the final follow-up (2- to 5-year) compared with those at baseline were observed (p＜0.0001 for all outcomes). Compared with isolated removal of calcific deposits, combined rotator cuff repair led to worse postoperative 3-month and 6-month VAS (p=0.004 and p=0.026, respectively) and 3-month ASES scores (p=0.012) but better 24-month and final VAS (p=0.035 and p=0.007, respectively) and ASES (p=0.034 and p=0.020, respectively) scores. MRI scans at the final follow-up showed significantly better outcomes in patients with rotator cuff repair (p=0.021). Conclusions Arthroscopic removal of calcific deposits is safe and effective for treating CT. Compared with isolated debridement, combined rotator cuff repair led to worse short-term but better medium- to long-term improvements in pain, function and integrity of tendons.